Local Automorphisms and Local Superderivations of Model Filiform Lie Superalgebras - Yuqiu Sheng; Wende Liu; Yang Liu (Journal of Mathematics)
In this paper, we give the forms of local automorphisms (resp. superderivations) of model filiform Lie superalgebra Ln,m in the matrix version. Linear 2-local automorphisms (resp. superderivations) of Ln,m are also characterized. We prove that each linear 2-local automorphism of Ln,m is an automorphism.